2010
DOI: 10.1093/heapro/daq056
|View full text |Cite
|
Sign up to set email alerts
|

Applying the social cognitive perspective to volunteer intention in China: the mediating roles of self-efficacy and motivation

Abstract: When predicting volunteer intention, much attention is paid to the volunteer organization environment (VOE). Given that self-efficacy and motivation have emerged as important predictors of volunteer intention, we adopted a combination of ideas of Bandura's social cognitive theory and Ajzen's theory of planned behavior integrating VOE, self-efficacy and motivation to examine their effects on volunteer intention and to determine whether self-efficacy and motivation mediate the relationship between VOE and volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 20 publications
5
29
1
Order By: Relevance
“…This result goes in line with those from other studies concerning paid work settings (Laguna et al, 2017;Schaufeli & Salanova, 2007;Xanthopoulou et al, 2009). Our findings confirmed the prominent role of self-efficacy in volunteering, that was suggested by other study findings as well (Wang et al, 2010). Self-efficacy is considered to be one of the personal resources that help people to impact upon and successfully control their working environment (Bandura, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result goes in line with those from other studies concerning paid work settings (Laguna et al, 2017;Schaufeli & Salanova, 2007;Xanthopoulou et al, 2009). Our findings confirmed the prominent role of self-efficacy in volunteering, that was suggested by other study findings as well (Wang et al, 2010). Self-efficacy is considered to be one of the personal resources that help people to impact upon and successfully control their working environment (Bandura, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Volunteer self-efficacy is defined as the ability or confidence to do volunteering activities in various situations (Wang, Wei, Harada, Minamoto, Ueda, Cui, Zhang, Cui, Ueda, 2010). It turned out to be related to volunteers' actions direction, their effort put in performance, as well as how and for how long they will persevere in the face of an adversity (Wang et al, 2010). The stronger the volunteers' self-efficacy, the stronger is their intention to complete a behavior and to achieve goals.…”
Section: Self-efficacy and Engagementmentioning
confidence: 99%
“…The results also demonstrated that the CSES could discriminate between the groups; that is, the scores of all the CSES factors and sub-scales in the CVOL group were higher than those in the GEN group (Table 4). This finding is also consistent with outcomes that volunteers have advantages over other citizens in terms of physical activity [42], mental health [43], self-rated health [44], and general self-efficacy [31]. …”
Section: Discussionsupporting
confidence: 85%
“…Second, the community’s beliefs about its capacity for achievement are a primary indicator of its potential ability to prevent social isolation of older people. Members of the general population are expected to be the primary resource for prevention, while community volunteers are expected to promote prevention in a variety of community health networks and organizations [31]. …”
Section: Introductionmentioning
confidence: 99%
“…More specifically, authors reported the need for further research on volunteers’ intentions and how or why people become and stay a volunteer. 16 Indeed, we know relatively little about how volunteers perceive job satisfaction, about their long-term engagement and about how this can be improved. 17 …”
Section: Introductionmentioning
confidence: 99%